Inżyniersko-geologiczne, środowiskowe i geotechniczne badania wałów przeciwpowodziowych w dolinach nizin środkowopolskich = Engineering-geological, environmental and geotechnical investigations of flood embankments in middle Poland lowland river valleys - Kołodziejczyk, Urszula; Kowalski, Witold Cezariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Passed investigations of flood-embankments stale during flood high wave passing and immediately after her passage in July 1997 showed lacks in their preservation in long periods between floods and shortcomings in flood- rescue action organization.
Keywords: powódź; Nizina Środkowopolska; badania